Homo consumerus - Wątroba, Wiesław (Homo consumerus, 2007)
Homo consumerus has been created by postindustrial capitalism. Being influenced by postmodern aesthetics, he has taken an advantage of globalization processes, and of technological progress aiming towards an informatization of everyday life. His future existence depends on a continuation of these processes. However, any kind of crusades against democracy, free market regime, or against contemporary consumer culture, and attempts of monopolization of the consumer markets by multinational corporations can reverse trends of globalization and glocalization. As a result, these tendencies can orginate an evolution of social perception of needs at their original form, rooted in the epoch of industrial caspitalism.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (15); 2007; nr 1166, s. 60-74